A Case Report of Transient Cortical Blindness After Angiography. Issue 3 (May 2017) - Chen, Chih Yen; Chen, Chi Jen; Tseng, Ying Chi
Abstract : Introduction: Transient cortical blindness (TCB) is a rare complication after angiography and is proposed to be related to contrast extravasation. We present the first case of TCB after angiography that was evaluated using serial arterial spin-labeling magnetic resonance perfusion (ASLMRP) and susceptibility-weighted imaging (SWI). Case Report: A 65-year-old woman with dyslipidemia who had been treated for left vertebral artery dissection 3 months previously presented with dizziness and right hemiparesis. Magnetic resonance imaging of the brain revealed suspected dissection of the V4 segment of the left vertebral artery. Cerebral angiography was performed using a total of 46 mL of nonionic contrast material. Approximately 3 hours after the procedure, the patient started complaining of a slight headache and nausea along with bilateral cortical blindness. The 6-hour ASLMRP and SWI of the brain, respectively, revealed hypoperfusion and increased oxygen extraction fraction in the bilateral occipital lobes. The patient gradually regained vision over the next 12 hours, and follow-up ASLMRP and SWI revealed normal perfusion and normal SWI findings, respectively. Conclusions: Hypoperfusion on ASLMRP and increased oxygen extraction fraction on SWI results derived for a patient presenting with TCB were demonstrated. Thus, we hypothesize that endothelin-related vasoconstriction is a pathophysiologic mechanism for TCB. To the best of our knowledge, this report is the first to describe ASLMRP and SWI findings in TCB after angiography.